ANALISIS NILAI TAMBAH BAWANG GORENG PADA UD. SAFARI BAWANG GORENG DI KELURAHAN KEBUN TEBENG KOTA BENGKULU ; VALUE ADDED ANALYSIS ON FRIED ONION OF UD. SAFARI BAWANG GORENG IN KELURAHAN KEBUN TEBENG BENGKULU CITY - Zuhardi Perdana Putra; Reswita Reswita Reswita; Irnad Irnad Irnad (BPFP Faperta UNIB, 2018)
ABSTRACTAgroindustry is an agriculture based industry that has an important role in economic growth in Indonesia. One of the agricultural subsector is horticultural crops, namely onion. The need for onion consumption in Indonesia has always increased. In the Bengkulu city there is a company engaged in the industry of fried onions are